2002
DOI: 10.1016/s0960-9822(02)00813-8
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans Responds to Chemical Repellents by Integrating Sensory Inputs from the Head and the Tail

Abstract: The phasmids are bilateral sensory organs located in the tail of Caenorhabditis elegans and other nematodes. The similar structures of the phasmids and the amphid chemosensory organs in the head have long suggested a chemosensory function for the phasmids. However, the PHA and PHB phasmid neurons are not required for chemotaxis or for dauer formation, and no direct proof of a chemosensory function of the phasmids has been obtained. C. elegans avoids toxic chemicals by reversing its movement, and this behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
327
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(338 citation statements)
references
References 12 publications
9
327
1
1
Order By: Relevance
“…When the worms exposed to UV-A, this network system have partially damaged as the time of exposure increased. This was attributed to the depletion of the activity of ASH neurons (Sambongi et al 1999) or the increased activity of PHA and PHB phasmid neurons (Hilliard et al 2002). The osmosensation assay results also suggest the damage in neural network, since it is also chiefly mediated by ASH neurons (Srinivasan et al 2008).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…When the worms exposed to UV-A, this network system have partially damaged as the time of exposure increased. This was attributed to the depletion of the activity of ASH neurons (Sambongi et al 1999) or the increased activity of PHA and PHB phasmid neurons (Hilliard et al 2002). The osmosensation assay results also suggest the damage in neural network, since it is also chiefly mediated by ASH neurons (Srinivasan et al 2008).…”
Section: Discussionmentioning
confidence: 88%
“…Hilliard et al (2002) stated that sensation of a repellent placed on the tail region of the worm and subsequent reversal be mediated by a head-to-tail spatial map. When the worms exposed to UV-A, this network system have partially damaged as the time of exposure increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ablation of the ASE neurons reduces but does not completely abolish the ability of worms to chemotax towards a point source of aqueous attractants including NaCl, while perturbation of ASE function, together with ADF, ASG, and ASI results in a more complete defect [72] (Table 1). Intriguingly, it has been shown that in ASE-ablated animals, the ability to respond to decreases in salt concentration is abolished, [104] whereas animals continue to respond to concentration increases, perhaps via the ADF, ASG, and ASI neurons [77]. It will be interesting to determine whether the ability to respond to positive or negative changes in concentration is segregated to different chemosensory neurons, to the left/right members of a neuron pair, or is a property of downstream components of the chemosensory circuit.…”
Section: Navigating Towards or Away From A Chemicalmentioning
confidence: 99%
“…To date, no specific chemosensory functions have been assigned to the inner labial chemosensory neurons. However, the PHA and PHB phasmid chemosensory neurons may sense chemical repellents and antagonize ASH-mediated avoidance behaviors [104] (Table 1).…”
Section: Mapping Chemicals To Chemosensory Neuronsmentioning
confidence: 99%